The effect of positive and negative work-family interaction on exhaustion Does work social support make a difference? - Karatepe, Osman M. (Emerald Group Publishing Ltd, 2010)
Purpose - The purpose of this paper is to develop and test a conceptual model, which investigates the effects of work family conflict family work conflict work family facilitation and family work facilitation simultaneously on exhaustion This study also aims to examine work social support as a moderator in the relationship between two directions of conflict and facilitation and exhaustion Design/methodology/approach - Data for this study were collected from a judgmental sample of full time frontline employees of the four and five star hotels of Albania Respondents self administered the questionnaires A total number of 107 questionnaires were retrieved Findings - The results of the hierarchical multiple regression analysis demonstrate that both work family conflict and family work conflict amplify exhaustion The results also indicate that work social support buffers the relationship between work family conflict and exhaustion and strengthens the negative relationship between work family facilitation and exhaustion Research limitations/implications - In future studies, longitudinal research designs should be employed to draw causal inferences regarding the relationships examined in the current study Though common method bias was checked with Harman's single factor test using confirmatory factor analysis gathering data from multiple sources would minimise problems associated with common method bias Practical implications - Hotel managers in Albania should benefit from establishing a family supportive work environment to enable their employees to manage their work and family roles effectively Training programs should be organised to teach employees and their supervisors concerning the critical importance of support surfacing from coworkers and supervisors in alleviating the detrimental impact of work family conflict on exhaustion and increasing the negative association between work family facilitation and exhaustion Originality/value - The paper adds to the compendium of knowledge by examining the aforementioned relationships via data gathered from a sample of full time frontline hotel employees in Albania
Keywords: Albania; Hotels Employees Family life